Desenvolvimento pós-embrionário da morfologia externa dos Mantodea (Insecta: Dictyoptera) - Araujo, Marcus Vinicius Scherrer de (2020)
The nymph stage of Mantodea represents approximately 50-60% of their total lifespan. Still, compared to the adult form, nymphs have historically received less attention in studies on the group. The biggest knowledge gap seems to be the